An Accident Analysis during the Covid-19 Pandemic in Indonesia uses the Accident Rate Method - Roselina Rahmawati; M Mukhlisin; Leily Fatmawati; Yustinus Eka Wiyana; Teguh Mulyo Wicaksono (Jurnal Teknik Sipil)
Abstract